Tacrolimus to belatacept conversion in proteinuric kidney transplant recipients - Efe, Orhan; Al Jurdi, Ayman; Eiting, Morgan Mabey; Marks, Christine Rogers; Cote, Mariesa Ann; Wojciechowski, David; Safa, Kassem; Gilligan, Hannah; Azzi, Jamil; Goyal, Nitender; Raynaud, Marc; Loupy, Alexandre; et al. (Frontiers in Immunology, 2024)
BackgroundProteinuria is associated with worse allograft outcomes in kidney transplant recipients (KTRs) and treatment strategies are limited. We examined the outcomes of calcineurin inhibitor (CNI) to belatacept conversion in proteinuric KTRs.MethodsIn a pilot phase II single-arm multicenter prospective trial, we recruited adult KTRs >6 months post-kidney transplantation with an estimated glomerular filtration rate (eGFR) ≥30 ml/min/1.73m2 and proteinuria >1 g/day. Patients were converted from CNI to belatacept. The primary outcome was a 25% reduction in proteinuria at 12 months.ResultsA total of 15 KTRs were recruited who had pre-conversion median (interquartile range) proteinuria of 1.8 (IQR 1.4 – 3.5) g/g and estimated glomerular filtration rate (eGFR) of 48 (IQR 32 – 52.5) ml/min/1.73m2. At 12 months post-conversion, median proteinuria was 1.4 (IQR 0.4 – 2.2) g/g (P = 0.068) and eGFR was maintained at 43 (34 – 54.5) ml/min/1.73m2. The primary outcome of at least a 25% reduction in proteinuria occurred in 53% (8/15) at 12 months. Abbreviated IBOX scores predicting 7-year graft survival were also stable at 1-year post-conversion compared to baseline. At extended follow-up at 5 years, both proteinuria and eGFR remained stable at 0.69 (0.24 – 2.15) g/g and 39 (31 – 57) ml/min/1.73m2, respectively.ConclusionsCNI to belatacept conversion was associated with preserved allograft function in KTRs with significant proteinuria. These findings need to be confirmed in a larger randomized clinical trial.Clinical trial registrationhttps://clinicaltrials.gov/, identifier NCT0232740.